3-(2-Formylphenoxy)propanoic acid - Collas, Alain (International Union of Crystallography, 2010)
In the structure of the title compound, C(10)H(10)O(4), the carboxyl group forms a catemer motif in the [100] direction instead of the expected dimeric structures. The carboxylic acid group is found in the syn conformation and the three-dimensional organization in the crystal is based on C—H⋯O and O—H⋯O interactions.